An Impossible Prayer: Ethics between Performative and Constative. Issue 2 (November 2021) - Aldieri, Eric
Abstract : This article takes up the blurred distinction between performative and constative utterances in an effort to develop a quotidian and idiomatic conception of prayer as perjurious testimony. Focusing on a passage in the recently published Le parjure et le pardon seminars, I argue that a quotidian and idiomatic conception of prayer is one whose function interminably oscillates between constative and performative, rendering the distinction between these two uses of language indiscernible. This oscillation plays not to prayer's detriment, but instead serves as the animating force behind prayer and the impossible ethical desire prayer expresses. The impossibility of a prayer whose desire is rendered perjurious by the state of affairs from which it emerges opens onto a number of political, ethical, and theological concerns that the second half of the paper addresses. By reading Simone Weil's reflections on the 'Our Father' in light of Derrida's considerations above, I argue that prayer's impossibility is a condition of possibility for its ability to produce real effects in the world it betrays.